Impact of Stator Resistance Unbalance on the Efficiency and Torque of Three-Phase Induction Motor - Muhamad Vickry Almuhtadi Billah; Siti Anisah; Parlin Siagian (INFOKUM, 2026)
Three-phase induction motors are key components in industrial power systems, but their performance is susceptible to internal disturbances such as stator resistance imbalance caused by aging, overheating, or manufacturing defects. This study aims to systematically analyze the impact of stator resistance imbalance on the efficiency and torque characteristics of squirrel cage rotor induction motors using equivalent circuit-based mathematical modeling. Unlike previous studies that used external resistors, this study modifies the stator resistance parameters directly in the model to represent more realistic internal degradation. Simulations were performed on a 3.73 kW, 400 V, 50 Hz motor with resistance imbalance variations from 0% to 20%. The results show that the imbalance causes uneven current distribution and an increase in stator copper losses of up to 5.94% at 20% conditions, although the percentage of current imbalance remains below 1%. As a result, the efficiency decreases linearly from 92.97% to 92.62%, while the mechanical torque experiences a small decrease from 95.88 Nm to 95.28 Nm. This phenomenon also has the potential to increase torque ripple and uneven heating. This study demonstrates that stator resistance imbalance, even small ones, has a significant impact on motor performance and lifespan, and therefore needs to be considered in predictive maintenance strategies and energy efficiency optimization.